2006
DOI: 10.1111/j.1600-0722.2006.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone on oral cells compared with established antimicrobials

Abstract: Ozone has been proposed as an alternative antiseptic agent in dentistry based on reports of its antimicrobial effects in both gaseous and aqueous forms. This study investigated whether gaseous ozone (4 x 10(6) microg m(-3)) and aqueous ozone (1.25-20 microg ml(-1)) exert any cytotoxic effects on human oral epithelial (BHY) cells and gingival fibroblast (HGF-1) cells compared with established antiseptics [chlorhexidine digluconate (CHX) 2%, 0.2%; sodium hypochlorite (NaOCl) 5.25%, 2.25%; hydrogen peroxide (H(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
1
25

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(152 citation statements)
references
References 32 publications
5
114
1
25
Order By: Relevance
“…The results of the research by Huth et al also proved greater positive effects of ozonated water on gum cells in comparison with those of other solutions (40). Although there is a lack of research on the effect of ozonated water on the prevention of VAP infection, there is literature on the relationship between VAP and oral care and the number of oral microorganisms (1,12), and the application of ozonated water to eliminate many of such microorganisms (23,34,41).…”
Section: Discussionmentioning
confidence: 97%
“…The results of the research by Huth et al also proved greater positive effects of ozonated water on gum cells in comparison with those of other solutions (40). Although there is a lack of research on the effect of ozonated water on the prevention of VAP infection, there is literature on the relationship between VAP and oral care and the number of oral microorganisms (1,12), and the application of ozonated water to eliminate many of such microorganisms (23,34,41).…”
Section: Discussionmentioning
confidence: 97%
“…25 The ozone treatment is painless and increases the patients' tolerability and fulfillment with minimal adverse effects. Most of the published articles considering the use of ozone in dentistry have been in relation to its antimicrobial effects [26][27][28] . Also, there is insufficient evidence in the application of ozone in oral and maxillofacial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…66 Hems et al 67 concluded that ozone in solution has antibacterial effect against planktonic E. faecalis; however, it was not effective in a biofilm environment unless displaced into surrounding medium by using agitation. It was also shown that gaseous ozone was not effective on biofilm of E. faecalis.…”
Section: -62mentioning
confidence: 99%